Family health education in improving the knowledge and attitude of flood emergency response in vulnerable groups - Adriani, Sri Wahyuni; Indriyani, Diyan; Elsa Apriani, Divia; Hariyadi, Chelzy Ferdina; Haryanti, Dwi Yunita; Dlamini, Lindelwa Portia (University of Muhammadiyah Malang, 2026)
Introduction: The community’s emergency response attitude before a disaster has not yet become a concern for the community. Communities, especially those living in disaster-prone areas, tend to ignore emergency response attitudes. Objectives: This study aims to provide health education programs through home visits, simulations, and mentoring activities to increase the community’s knowledge and attitudes regarding emergency response to flood disasters. Methods: A quasi-experimental research design with a control group and a pre-test-post-test design was used. The research population was a vulnerable group (pregnant women, mothers of toddlers, the elderly, and people with disabilities) totaling 321 people. The selected sample comprised 120 participants, with 60 in each intervention and control group. The sampling method used was stratified random sampling. Results: There were significant differences in knowledge and attitudes towards disaster emergency response between the intervention and control groups (p=0.032), emergency plans (p=0.008), disaster warning systems (p=0.020), and the ability to mobilize resources (p=0.015). The community preparedness index also increased (p=0.002).Conclusions: Ongoing education programs were the first step toward making the community self-sufficient. Improving the community’s knowledge and attitude toward emergency response will reduce the negative impact of a disaster if it occurs.